Kernel-PCA denoising of artifact-free protein NMR spectra - Stadlthanner, K. (2004)
Multidimensional 'H NMR spectra of hiomolecules dissolved in light water are contaminated by an intense water artifact. Generalized eigenvalue decomposition methods using congruent matrix pencils are used to separate the water artefact from the protein spectra. Due to the statistical separation process, however, noise is introduced into the reconstructed spectra. Hence Kernel - based denoising techniques are discussed lo obtain noise- and artifact - free 2D NOESY NMR spectra of proteins.